2010
DOI: 10.1167/iovs.09-4652
|View full text |Cite
|
Sign up to set email alerts
|

Association of POAG Risk Factors and the Thr377MetMYOCMutation in an Isolated Greek Population

Abstract: This village had a high frequency of glaucoma, with 12% of the participants aged 10 to 95 years having the disease. In this cohort, the Thr377Met MYOC mutation was significantly associated with both high intraocular pressures and high vertical cup-to-disc ratios. No association was found with central corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Myocilin is a member of the olfactomedin protein family with an N-terminal leucine zipper motif and a large C-terminal olfactomedin homology domain (Box 2). Association studies and analyses of pedigrees have shown that mutations in myocilin, especially its olfactomedin domain, are associated with a substantial fraction (>10 %) of juvenile onset glaucoma patients [2,6,7] and a smaller portion (~4%) of adult POAG cases in African-American [8], Canadian [9], Indian [10], Japanese [11], Greek [12], South African [13], Brazilian [14], Peruvian [15], Ghanaian [16], Swiss [17], and Dutch [18] populations. However, in some populations, including Moroccan [19], Middle Eastern [20], and Finnish populations [21], case-control studies failed to identify POAG-associated polymorphisms in myocilin.…”
Section: Glaucoma and Myocilinmentioning
confidence: 99%
“…Myocilin is a member of the olfactomedin protein family with an N-terminal leucine zipper motif and a large C-terminal olfactomedin homology domain (Box 2). Association studies and analyses of pedigrees have shown that mutations in myocilin, especially its olfactomedin domain, are associated with a substantial fraction (>10 %) of juvenile onset glaucoma patients [2,6,7] and a smaller portion (~4%) of adult POAG cases in African-American [8], Canadian [9], Indian [10], Japanese [11], Greek [12], South African [13], Brazilian [14], Peruvian [15], Ghanaian [16], Swiss [17], and Dutch [18] populations. However, in some populations, including Moroccan [19], Middle Eastern [20], and Finnish populations [21], case-control studies failed to identify POAG-associated polymorphisms in myocilin.…”
Section: Glaucoma and Myocilinmentioning
confidence: 99%